Identifying Students’ Misconceptions in Chemical Equilibrium Using a Five-Tier Multiple-Choice Diagnostic Test - Putri Adita Wulandari; Muhammad Fikri; Abdullah Abdullah; Tiara Swastika Putri (Jurnal Zarah, 2026)
This study aims to identify the profile of students' misconceptions on chemical equilibrium and to determine the sources of these misconceptions. This study used a descriptive method with quantitative and qualitative approaches and was conducted at SMA Negeri 7 Pekanbaru. The research subjects involved 187 11th-grade students who had studied chemical equilibrium. Data collection was conducted using a five-level diagnostic test instrument consisting of 15 questions and structured interviews. The results showed that the average percentage of students experiencing misconceptions was relatively low, at 20.93%. Analysis of the sources of misconceptions showed that the main cause of misconceptions came from students' personal thoughts, with a percentage of 24.15%. Other contributing sources included friends (20.66%), teachers (18.78%), the internet (18.35%), and books (18.06%). These findings indicate that students' misconceptions are more influenced by independent constructions of understanding that do not align with scientific concepts than other external factors.